KUALITAS PELAYANAN SURAT KETERANGAN TANDA LAPORAN KEHILANGAN (SKTLK) DILIHAT DARI ASPEK RESPONSIVENESS PADA POLSEK HARUAI KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Public services are the full responsibility of the government. The primary purpose of public services is to provide services that meet service standards and follow community expectations. However, in practice, there are still public services that do not meet the standards of public services and the quality of human resources and aspects of supporting services that have not been adequate. This is known from direct and indirect complaints from the public as service applicants, for example, through social media, print media, and electronic media. Some of these complaints include public service agencies that do not provide time certainty, complicated procedures, extortion, the attitude of officers who are less responsive to the public who need services or procedures, and service requirements that are not transparent. This can affect the quality of service in the relevant institutions. The police are one of the government's civil institutions that also provide public services to the community through services and goods directly or administratively. One form of public administrative service is the creation of a Loss Report Certificate (SKTLK). This study aimed to determine how the Service Quality of Loss Report Certificate (SKTLK) was seen from the Responsiveness Aspect at the Haruai Police Station, Tabalong Regency. The method used in this research is a qualitative descriptive approach. The data collection technique used interviews with five sources. The data analysis technique used is the inductive model. The results of research conducted by researchers in the community of Haruai District, Tabalong Regency, about the quality of service for Lost Report Certificates at the Haruai Sector Police, Tabalong Regency, it can be concluded that the quality of service for Loss Report Certificates is seen from the responsiveness aspect of the Haruai Sector Police, Tabalong Regency. Keywords: Quality, Service, SKTLK .